Reconstructing the Empowerment Model for Bajo Community Based on Local Wisdom in the Pomalaa Nickel Industrial Area - Irawati Irawati; Rahmat Hidayat; Syamsir Syamsir; Sultan Abadi (CV. Social Politic Genius (SIGn), 2025)
The massive expansion of the nickel mining industry in the Pomalaa area has led to marginalization and exclusion of the Bajo community from marine spaces. Instead of alleviating poverty, the highly hierarchical corporate social responsibility programs actually create pseudo-empowerment practices that perpetuate corporate domination and the material dependency of coastal communities. This research aims to deconstruct these power relations and ecological inequalities while simultaneously reconstructing the design of a participatory, sustainable, multi-stakeholder empowerment model. This research employs a qualitative, critical-paradigm approach with a case study design. Primary data sourced from limited participatory observation and in-depth interviews with Bajo fishermen, activists, and community leaders were interactively analyzed using a discourse deconstruction framework instrument. The results indicated that corporate regulatory manipulation has deprived fishermen of traditional fishing grounds and destroyed ecological carrying capacity. To counter this hegemony, Bajo local wisdom in the form of a traditional marine conservation system (bapongka) and an egalitarian brotherhood principle (sama bajau) is institutionalized as the basis of agency towards an active society. These cultural values are subsequently operationalized into a multi-stakeholder empowerment model that synergizes the roles of the government as a facilitator, the private sector as a contributor, higher education institutions as technology innovation providers, and non-governmental organizations as advocacy mentors. In conclusion, the systemic integration among actors centered on the fishermen subjects is capable of generating an independent community enterprise. In practice, this study recommends that local government authorities undertake juridical interventions to formulate regulations protecting traditional fishing zones, thereby restoring the sovereignty and welfare of the Bajo community.